The Effect of Yoga Exercise on Reducing Blood Pressure among Elderly with Hypertension - Aura Rosse Maharani; Nurul Fithriati Haritsah; Yoga Handita Windiastoni; Noerdjannah (Journal of Epidemiology and Public Health, 2024)
Background: Hypertension is a silent killer with no symptoms. One of the non-pharmacological treatments used is yoga exercises. This study aims to determine yoga exercise on reducing blood pressure among elderly with hypertension.Subjects and Method: This study is a one-group pre and post-test conducted at the Tohudan Colomadu Karanganyar Elderly Posyandu from March to April 2024. A total of 19 elderly people aged 50 to 70 years were selected using purposive sampling. The dependent variable in this study was a decrease in blood pressure. The independent variable in this study was yoga gymnastics. The study was conducted by measuring blood pressure before and after yoga exercises using a sphygmomanometer. The collected blood pressure data was analyzed using SPSS.Results: Average systolic blood clearance (Mean= 148.53; SD=6.62) and diastolic blood pressure (Mean= 93.26; SD= 2.05) before the intervention was higher than systolic blood pressure (Mean= 141.53; SD= 7.32) and diastolic blood pressure (Mean= 87.37; SD=2.29) after the intervention, and the results were statistically significant (p=<0.001).Conclusion: Systolic blood pressure and diastolic blood pressure before intervention were higher than systolic blood pressure and diastolic blood pressure after intervention.